Cumulative incidence and spatial distribution of dogs exposed to toxoplasma gondii - Olbera, Alisson Vinícius Gimenes [UNESP]; Fornazari, Felipe [UNESP]; Babboni, Selene Daniela [UNESP]; Rossi, Rodolfo Santos [UNESP]; Sevá, Anaiá Paixão; Latosinski, Giulia Soares [UNESP]; da Silva, Mariana Aimee Ramos Xavier [UNESP]; Modolo, Jose Rafael [UNESP]; Langoni, Helio [UNESP] (FapUNIFESP (SciELO), 2020)
Toxoplasma gondii is one of the most important protozoa parasites worldwide. Although many seroprevalence studies have been performed in domestic and wild species, data on the cumulative incidence and the spatial distribution of T. gondii in animals are extremely scarce. In the present study, dogs from Botucatu municipality, São Paulo state, were followed for one year and their blood samples were collected on three moments: days 1, 180, and 360. The sera were submitted to the immunofluorescence antibody test (IFAT) to detect IgG antibodies to T. gondii. Age and sex were compared with IFAT results through statistical tests. Spatial analysis was used to detect clusters of seropositive dogs. Among the 350 dogs that were seronegative on day 1, 53 became seropositive in subsequent samplings; thus, cumulative incidence was 15.1% exposed dogs/year. Age and sex were not associated with serological results. The spatial analysis revealed that seropositive dogs were distributed in all the studied areas, with a significant cluster in a zone with poor sanitary conditions and low socioeconomic status. T. gondii is frequent and widely distributed in the urban area of Botucatu, and impoverished areas are possibly associated with high levels of environmental contamination by this parasite.
Incidência cumulativa e distribuição espacial de cães expostos a toxoplasma gondii
Keywords: IgG; Immunofluorescence antibody test; Parasitology; Toxoplasmosis; Zoonosis